Lack of association between the 807 C/T polymorphism of glycoprotein Ia gene and post-treatment platelet reactivity after aspirin and clopidogrel in patients with acute coronary syndrome - Cuisset, Thomas; Frere, Corinne; Quilici, Jacques; Morange, Pierre-Emmanuel; Saut, Noémie; Romero-Barra, Marie; Camoin, Laurence; Lambert, Marc; Juhan-Vague, Irène; Bonnet, Jean-Louis; Alessi, Marie-Christine (Thrombosis and Haemostasis, 2007)
Variability in platelet response to antiplatelet therapy and its clinical relevance have been well described. However, the underlying mechanisms remain unclear. It was the aim of the present study to assess whether the response to aspirin and clopidogrel may be influenced by the 807 C/T polymorphism of the glycoprotein Ia (GpIa) gene in patients with non-ST elevation acute coronary syndrome (NSTE ACS). Six hundred one NSTE ACS patients were included in our study and were divided into three groups: CC homozygotes, CT heterozygotes ad TT homozygotes. All patients received loading doses of 600 mg clopidogrel and 250 mg aspirin at least 12 hours before blood samples were drawn. Post-treatment platelet reactivity was assessed by post treatment ADP 10 µM-induced platelet aggregation (ADP-Ag), VASP phosphorylation (PRI VASP) and P-selectin expression. Non-response to dual antiplatelet therapy was defined by high post-treatment platelet reactivity (HPPR= ADP-Ag>70%). Significant variability in the distribution of platelet parameters was observed in the overall study population. No significant difference in platelet parameters profiles was observed within patients having the same genotype, for ADP-Ag (p=0.33), PRIVASP (p=0.72) and P-selectin expression (p=0.37). The genotype frequencies of the 807 C/T polymorphism of the GpIa gene were similar in responders and non-responders defined by persistent HPPR (p=0.104). In conclusion, our study did not show any influence of 807 C/T polymorphism of GpIa gene on post-treatment platelet reactivity assessed by ADP-Ag, PRI VASP or P-selectin expression in 601 NSTE ACS patients.
Keywords: ADP receptors; polymorphisms; coronary syndrome; collagen receptors; antiplatelet agents